Dechlorination of polychlorobiphenyl degradation metabolites by a recombinant glutathione S-transferase from Acidovorax sp. KKS102 - Shehu, Dayyabu; Alias, Zazali (Wiley Open Access, 2019)
A glutathione S-transferase (GST) with a potential dehalogenation function against various organochlorine substrates was identified from a polychlorobiphenyl (PCB)-degrading organism, Acidovorax sp. KKS102. A homolog of the gene BphK (biphenyl upper pathway K), named BphK-KKS, was cloned, purified and biochemically characterized. Bioinformatic analysis indicated several conserved amino acids that participated in the catalytic activity of the enzyme, and site-directed mutagenesis of these conserved amino acids revealed their importance in the enzyme's catalytic activity. The wild-type and mutant (C10F, K107T and A180P) recombinant proteins displayed wider substrate specificity. The wild-type recombinant GST reacted towards 1-chloro-2,4-dinitrobenzene (CDNB), ethacrynic acid, hydrogen peroxide and cumene hydroperoxide. The mutated recombinant proteins, however, showed significant variation in specific activities towards the substrates. A combination of a molecular docking study and a chloride ion detection assay showed potential interaction with and a dechlorination function against 2-, 3- and 4-chlorobenzoates (metabolites generated during PCB biodegradation) in addition to some organochlorine pesticides (dichlorodiphenyltrichloroethane, endosulfan and permethrin). It was demonstrated that the behavior of the dechlorinating activities varied among the wild-type and mutant recombinant proteins. Kinetic studies (using CDNB and glutathione) showed that the kinetic parameters K m , V max , K cat and K m /K cat were all affected by the mutations. While C10F and A180P mutants displayed an increase in GST activity and the dechlorination function of the enzyme, the K107T mutant displayed variable results, suggesting a functional role of Lys107 in determining substrate specificity of the enzyme. These results demonstrated that the enzyme should be valuable in the bioremediation of metabolites generated during PCB biodegradation. © 2018 The Authors. Published by FEBS Press and John Wiley & Sons Ltd.